The treasure of Środa as a source for research on medieval symbols and migrations - Wachowska, Małgorzata; Wachowski, Krzysztof (Archaeologia Historica Polona, 2020)
Analysis of the symbolism of engagements, wedding ceremonies and wedding celebrations does not allow us to strictly define the symbols associated with these occasions. It is also difficult to determine the variation in symbolism in time and space. Nevertheless, a list of certain symbols has been established: the hand-in-hand gesture, the ring and the garland. This last seems to be particularly important during the wedding feast. The crown and the garland are, first of all, specifically bridal headgear; the crown is also worn during the wedding ceremony but is not a symbol of the ceremony. In the Kingdom of Poland, and perhaps also in other areas, if a coronation and wedding took place simultaneously, a garland was marked on the bride’s crown. Meanwhile, an eagle on the crown or on other dress accessories probably only elevated the status of these artefacts and cannot be heraldic. Archaeological discoveries also allow to state that diadems with eagles holding rings in their beaks – like a specimen from Środa Śląska – were also made of tin-lead alloys. Despite the incredible abundance of silver treasures in the early Middle Ages on Polish lands, which largely resulted from the migration of Scandinavians, it is hard to talk about the emergence of new financial market instruments at that time, although some effects are visible in the commercial culture. Only in the late Middle Ages, thanks to the German, Teutonic and Hansa colonisation, and the migration of Jews, credit appears, the material effect of which is bond hoards, and in the 15th century, commercial paper – a modern financial market tool. All this evidences that medieval hoards are also a source of research on migration.